Territorialidade e pesca: atualidades e tradições no uso dos recursos pesqueiros na comunidade litorânea da praia da Pipa Rio Grande do Norte - Machado, Janaína Farina (2011)
The need for sustainability in the exploitation of natural resources in coastal areas has been out in recent years, as well as the social and cultural sustainability of traditional communities in these regions. Coastal and estuarine wild areas are influenced directly or indirectly by a set of human activities such as artisanal fishing. Therefore, there is a demand for an integrated design of these areas and according to the landing values, a pattern of unsustainable development of national marine fishing activity. The study was conducted in the coastal community of Praia da Pipa, Tibau do Sul municipality, RN, between june 2009 and june 2010 and aimed to characterize the fishery performed, its socio-economic strategies and fishing areas, as well as to identify ichthyofauna, to assess the sustainability of the major resources and to identify cultural traits related to artisanal fisheries, their problems and prospects; linking tradition and the present fishing activity carried out in the community. For this study, a total of 67 structured interviews were collected, including qualitative and quantitative data. A total of 133 fish landings and direct observations were performed. Informants were identified according to one of the following categories: fishermen, vessel masters and members of the local population with offspring. Applications SPSS 10.0, Paint.Ink and Microsoft Office Excel 2007 were used for tabulation and analysis of results. Local fishermen are, on average, 25 years fishing, have 40 years old and the average monthly income is up to 03 minimum wages. The local fleet consists of 20 vessels, that uses different line sizes and types of networks, operating in 21 fishing grounds and showing a reduction in the vessel numbers by 66% in the last decade. We recorded 76 species of fish, captured by the local fleet and the top 5 were quantitatively analyzed serra spanish mackarel (Scomberomorus brasiliensis), little tunny (Euthynnus alleteratus), yellowtail snapper (Ocyurus chrysurus), red snapper (Lutjanus analis) and common snook (Centropomus undecimalis), accounting for 46,5% of production in the period. The capture of these species was composed mostly of adults. Data analysis showed a significant decrease of the local fishing activity over the last decade due to the weakness displayed by the political-social category, the devaluation of local knowledge and the emergence of new sources of income through increased tourism. The characteristics of the fishing community suggest it to pass through significant changes as the appreciation of their cultural and traditional aspects. We identified a tendency to sustainability of main species caught, suggesting that public policies to be adopted locally comply with the current characteristics of fishing undertaken in the community and knowledge of fishermen related to the environment, allowing environmental, as well as social and cultural sustainability of the community involved.